Supervision of Subdistrict Heads as Temporary Deed Making Officials in the Indonesian Positive Law Perspective - Saputra, Tri Eka; Rustan, Rustan (Manunggal Halim Jaya, 2023)
This article discusses supervision of the sub-district head as an official who makes temporary land deeds who violates statutory provisions. The aim is only to provide an overview of the supervision of sub-district heads carried out by the Board of Trustees and Supervisors of officials who make land deeds. The research method used in this article is normative legal research. The results of the research illustrate that supervision by the PPAT supervisory board and supervisors in carrying out guidance and supervision of PPATS, the supervision is not yet comprehensive. This is in Ministerial Regulation Number 2 of 2018, PPAT Guidance and Supervision has not been able to answer substantively regarding the guidance and supervision by PPATS where the position of a PPATS is ex officio so that the guidance and supervision both internally and externally carried out by the National Land Agency is only functional.